Colletotrichum paridis sp. nov., a novel endophytic species on Paris polyphylla var. chinensis - Cui, Hua-Wei; Malik, Kamran; Xue, Long-Hai; Wei, Xue-Kai (Phytotaxa, 2024)
The genus Paris is a crucial medicinal herb, widely cultivated in East Asia and Europe. In 2017 a novel Colletotrichum species was isolated from leaf lesions with grey mould of Paris polyphylla var. chinensis in Sichuan Province of China. Through single-spore technique, four isolates were obtained for characterization. Phylogeny inferred from multi-locus sequences of ITS, gapdh, act, tub2, chs-1, and his3, showed that these isolates represented a novel sister species to C. jinshuiense within the C. dematium complex. Morphologically, this new species produces larger conidia than those of C. jinshuiense and cultures on PDA show a noticeable pink ring. Tests showed that this species had no pathogenicity to the host plants. Based on phylogenetic, morphological, and pathogenicity data, we propose the name C. paridis sp. nov. for this new endophyte from P. polyphylla in China.